Author Details for the Research Article "Towards a Sociological Literature Review on m-Health Applications" - Shikha Jagarwal; Amithy Jasrotia (Shiraz University of Medical Sciences, 2024)
Background: For many trying to understand the sociology of technological artefacts and their influence in establishing human behaviour towards health, the study of m-Health applications becomes critical in the development of health and fitness behaviour among humans. M-Health is a growing field of study under 'Social Construction of Technology (SCOT)' wherein progress is witnessed in various categories such as the mobile application, developed to cater to the different needs of the digital health and fitness market.Methods: Through the scoping review under the broader category of a systematic literature review in the present paper, the aim is to understand the sociological construction and adoption of the health and fitness m-Health applications. For this purpose, the review contains peer-reviewed papers and articles, books, and other literature. These studies have been developed systematically and a comprehensive scope of further research  that takes into account the contextual transformation of these m-Health applications has culminated.Results: To d evelop b etter c onceptual i nnovations, t he idea of quantified self and research gaps are highlighted. Further, a wider scope for quantifying oneself can be expanded for studies in a developing country like India. The idea of m-Health application has revolved around various categories that take into consideration the formative needs of healthcare in a developing as well as a developed world.Conclusion: Through this paper, we study the need to broaden the sociological lenses that comprehend the construction of these applications within the social context and how they are reshaping the behavioural patterns of health and fitness among individuals.